The secret circle : the divide - Smith, L. J. (Lisa J.); Clark, Aubrey (Secret circle (New York, N.Y.), 2012)
A first installment in a new spin-off story arc finds Cassie relocating to New Salem, pursuing a romance with Adam, and assuming joint leadership over an elite coven of witches whose loyalty is tested as Cassie prepares to confront a latest evil force.